2010
DOI: 10.1097/moo.0b013e32833af8f8
|View full text |Cite
|
Sign up to set email alerts
|

Key issues in nasal reconstruction

Abstract: A large variety of sophisticated techniques continue to emerge with the goal of producing increasingly natural results for patients undergoing nasal reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The median forehead flap is widely used to reconstruct defects in all nose subunits with a wide range of sizes [ 8 ]. However, the most substantial drawback of this flap is the donor site scar that forms in the central forehead area, especially in Asian populations [ 9 ]. Unlike Caucasians, the nose of Asians generally has a flat, wide base of the bony pyramid, less muscle volume, and a flatter glabella [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The median forehead flap is widely used to reconstruct defects in all nose subunits with a wide range of sizes [ 8 ]. However, the most substantial drawback of this flap is the donor site scar that forms in the central forehead area, especially in Asian populations [ 9 ]. Unlike Caucasians, the nose of Asians generally has a flat, wide base of the bony pyramid, less muscle volume, and a flatter glabella [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…These areas include shallow, concave areas, such as the medial canthal area, or alar-facial sulcus, and areas with a firm base, which prevent wound contracture and distortion of surrounding tissue such as the forehead or upper nasal sidewall. 10,12,24,25 In one study of 95 patients who were healed by secondary intention, excellent results were found in small, superficial defects on concave surfaces. 26 To obtain optimal results, the wound must be kept clean and moist with petroleum or antibiotic ointment.…”
Section: Secondary Intentionmentioning
confidence: 99%
“… 3 , 5 However, the nose represents a complex anatomical region, in which small functional alterations can cause great harm to the patient. 6 Thus, the study of rhinoplasty techniques associated with those of septoplasty has gained prominence in referral otolaryngology services, which are regarded as professional generation centers, with the greatest responsibility for the training of these professionals. 2 , 4 …”
Section: Introductionmentioning
confidence: 99%